2007
DOI: 10.1139/s06-047
|View full text |Cite
|
Sign up to set email alerts
|

Methane oxidation in landfill cover soil; the combined effects of moisture content, nutrient addition, and cover thickness

Abstract: Oxidation of methane by methanotrophs in the landfill cover soil provides a source reduction for methane. Full factorial 23 experimental design using heterogeneous batch reactors was conducted to investigate statistically the individual and combined effects of soil moisture content, nutrient addition, and cover thickness on the CH4 oxidation process, during the migration through a landfill cover soil. Adding fertilizer as nutrient source to the 200 mm layer thickness of the landfill cover soil that contained 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 19 publications
0
21
0
2
Order By: Relevance
“…The reported values of landfill cover soils' CH 4 oxidizing efficiency vary widely in the literature. Albanna et al (2007) reported that increasing the soil layer thickness from 15 to 20 cm increased the CH 4 oxidation values from 29% to 35% for a soil with 15% moisture content without nutrient addition, from 34% to 38% for a soil with a 30% moisture content without nutrient addition, and from 75% to 81% for a soil with a 30% moisture content with nutrient addition. However, in investigating the effect of bio-cover on CH 4 oxidation at the Leon landfill in Florida, Stern et al (2007) found that the efficiency of CH 4 oxidation can reach 64% with biocover utilization, while only 30% efficiency was reported for the control cell.…”
Section: Factors Affecting Methane Oxidationmentioning
confidence: 99%
See 3 more Smart Citations
“…The reported values of landfill cover soils' CH 4 oxidizing efficiency vary widely in the literature. Albanna et al (2007) reported that increasing the soil layer thickness from 15 to 20 cm increased the CH 4 oxidation values from 29% to 35% for a soil with 15% moisture content without nutrient addition, from 34% to 38% for a soil with a 30% moisture content without nutrient addition, and from 75% to 81% for a soil with a 30% moisture content with nutrient addition. However, in investigating the effect of bio-cover on CH 4 oxidation at the Leon landfill in Florida, Stern et al (2007) found that the efficiency of CH 4 oxidation can reach 64% with biocover utilization, while only 30% efficiency was reported for the control cell.…”
Section: Factors Affecting Methane Oxidationmentioning
confidence: 99%
“…For simplicity, previous studies have reported that the CH 4 oxidation process in landfill cover soils is accomplished by methanotrophic bacteria (Abushammala et al, 2012;Huber-Humer et al, 2008;Albanna et al, 2007;Stern et al, 2007;Kettunen et al, 2006). Methanotrophic bacteria (Fig.…”
Section: Methane Oxidation Bacteriamentioning
confidence: 99%
See 2 more Smart Citations
“…Soils, more precisely the microorganisms living in soils, have been widely observed to have the unique ability of utilizing CH 4 as their carbon and energy source and oxidize it to CO 2 [5][6]. Landfi ll cover, where CH 4 is presented at high concentration and O 2 is partly available, has proven to possess impressive CH 4 oxidation potential [7][8][9][10][11][12][13][14]; recent study reported a mean value of 36 ±6% for CH 4 oxidation effi ciency [15], although the default value for this parameter set by IPCC and the USEPA is relatively low (0%-10%) [16].…”
Section: Introductionmentioning
confidence: 99%